High-Pitch Computed Tomography of the Lung in Pediatric Patients: An Intraindividual Comparison of Image Quality and Radiation Dose to Conventional 64-MDCT - Tsiflikas, I.; Thomas, C.; Ketelsen, D.; Seitz, G.; Warmann, S.; Claussen, C. D.; Schäfer, J. F. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: The aim of this study was to investigate frequencies of typical artifacts in low-dose pediatric lung examinations using high-pitch computed tomography (HPCT) compared to MDCT, and to estimate the effective radiation dose (Eeff).Materials and Methods: Institutional review board approval for this retrospective study was obtained. 35 patients (17 boys, 18 girls; mean age 112 ± 69 months) were included and underwent MDCT and follow-up scan by HPCT or vice versa (mean follow-up time 87 days), using the same tube voltage and current. The total artifact score (0 – 8) was defined as the sum of artifacts arising from movement, breathing or pulsation of the heart or pulmonary vessels (0 – no; 1 – moderate; 2 – severe artifacts). Eeff was estimated according to the European Guidelines on Quality Criteria for Multislice Computed Tomography. The Mann-Whitney U test was used to analyze differences between the patient groups. The Spearman's rank correlation coefficient was used for correlation of ordinal variables.Results: The scan time was significantly lower for HPCT compared to MDCT (0.72 ± 0.13 s vs. 3.65 ± 0.81s; p < 0.0001). In 28 of 35 (80 %) HPCT examinations no artifacts were visible, whereas in MDCT artifacts occurred in all examinations. The frequency of pulsation artifacts and breathing artifacts was higher in MDCT compared to HPCT (100 % vs. 17 % and 31 % vs. 6 %). The total artifact score significantly correlated with the patient's age in MDCT (r = – 0.42; p = 0.01), but not in HPCT (r = – 0.32; p = 0.07). The estimated Eeff was significantly lower in HPCT than in MDCT (1.29 ± 0.31 vs. 1.47 ± 0.37 mSv; p < 0.0001).Conclusion: Our study indicates that the use of HPCT has advantages for pediatric lung imaging with a reduction of breathing and pulsation artifacts. Moreover, the estimated Eeff was lower. In addition, examinations can be performed without sedation or breath-hold without losing image quality.Key points:• Fewer artifacts in pediatric lung imaging with HPCT• Reduced Eeff in HPCT• HPCT without sedation or breath-hold without loss of image qualityCitation Format:• Tsiflikas I, Thomas C, Ketelsen D et al. High-Pitch Computed Tomography of the Lung in Pediatric Patients: An Intraindividual Comparison of Image Quality and Radiation Dose to Conventional 64-MDCT. Fortschr Röntgenstr 2014; 186: 585 – 590
Keywords: thorax; CT; artifacts